2014
DOI: 10.1063/1.4897148
|View full text |Cite
|
Sign up to set email alerts
|

High temperature study of flexible silicon-on-insulator fin field-effect transistors

Abstract: Articles you may be interested inHot carrier effect on gate-induced drain leakage current in high-k/metal gate n-channel metal-oxidesemiconductor field-effect transistors Appl. Phys. Lett. 99, 012106 (2011) Unique method to electrically characterize a single stacking fault in silicon-on-insulator metal-oxide-semiconductor field-effect transistors

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…42,43,49,50,53 In all of those studies we consistently observed no noticeable electrical performance variation due to the ultra-thin silicon. Here we restrict the study to the ultra-thin silicon itself (later in this paper, we extend the discussion to crossbars metallic lines for current injection heat generation/dissipation effects, demonstrate representative functional devices on ultra-thin silicon, and report their performance characteristics and reliability aspects).…”
Section: A Fabricationmentioning
confidence: 59%
See 1 more Smart Citation
“…42,43,49,50,53 In all of those studies we consistently observed no noticeable electrical performance variation due to the ultra-thin silicon. Here we restrict the study to the ultra-thin silicon itself (later in this paper, we extend the discussion to crossbars metallic lines for current injection heat generation/dissipation effects, demonstrate representative functional devices on ultra-thin silicon, and report their performance characteristics and reliability aspects).…”
Section: A Fabricationmentioning
confidence: 59%
“…In the past, on ultra-thin silicon with deterministic pattern of porous network of vertical micro-air channels, we have demonstrated various functioning physical electronics including MIMCAPs, 41,42 MOSCAPs, [43][44][45][46] MOSFETs, 47 FinFETs 48,49 (including high temperature study 50 ), thermoelectric generators (TEGs), 51 and memristors 52 and have also reported their full performance analysis (both electrical and mechanical) [41][42][43][44][45][46][47][48][49][50][51][52] and their long term mechanical and electrical reliability and stability. 42,43,49,50,53 In all of those studies we consistently observed no noticeable electrical performance variation due to the ultra-thin silicon.…”
Section: A Fabricationmentioning
confidence: 99%
“…Using transfer printing technique, the micro/nano structures (Si, GaAs NWs or NRs) obtained using top-down or bottom-up approach are transferred over the desired flexible/rigid substrate using a PDMS stamp [33][34][35][36][37]. In an alternative transfer printing approach, the standard CMOS processed Si wafers were subjected to post-thinning of Si wafer and transferring [38][39][40]. CMOS compatibility opens up new avenues as the approach could be extended to obtain bendable chips with complex integrated circuits and eventually complete bendable sensing systems.…”
Section: A Transfer Printingmentioning
confidence: 99%
“…While maintaining large-scale production and prototyping rapidity, this flexible and translucent scheme demonstrates the potential to transform conventionally stiff electronic devices into thin, foldable ones without compromising long-term performance and reliability. [2][3][4][5] Recent research in flexible [6][7][8][9][10][11][12][13][14][15][16][17] and stretchable [18][19][20][21][22][23][24][25][26][27][28][29] electronics shows that flexibility has emerged as a central feature and game-changer, allowing not only for large-scale deployment of such devices in what is currently referred to as macroelectronics, 30 but also opening the possibility of integration of flexible electronics on mechanically flexible and reversibly bistable platforms. 31 Flexible display devices are arguably one of the most researched topics [32][33][34][35] in the scholarly world, and most products on the market are based on organic light-emitting diode (OLED) technology and active thin-film organic devices.…”
mentioning
confidence: 99%
“…The reversibly bistable platform (m ¼ 20 g; metal density (q) ¼ 10.09 g/cm 3 ; ultimate tensile strength (r ts ) in the range of 345-724 MPa; and modulus of elasticity in tension (Y Fe-C ) % 170 GPa) 47,48 was repeatedly accelerated toward a human hand, with an impact speed v 1 of approximately 4.45 m/s and an impact distance Dy of about 2.25 mm, resulting in an impact time Dt of roughly 500 ms and an impulsive force (RF) avg with a magnitude of almost 180 N during each impact cycle. We observed the accumulative effect of applying such impulsive forces and reported the results in relation to CIB.…”
mentioning
confidence: 99%